2019
DOI: 10.1097/md.0000000000017108
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes may be favorable biomarker and predictor of long-term outcome in patients with chronic heart failure

Abstract: Although some studies found that an increased monocyte count is a predictive, short-term marker of unfavorable outcomes for patients with acute heart failure (HF), others have reported that monocytosis predicts prolonged survival.The current follow-up study aimed to identify different monocyte count patterns and their prognostic association with HF outcomes.Baseline blood samples for complete blood counts, differential counts, renal function tests, and lipid profiles of 303 chronic HF patients (average NYHA cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…We found that the proportions of non-classical monocytes increased through the spectrum of AD from SMC to AD, while the intermediate monocyte subset increased only in MCI and AD patients at the expense of classical monocytes. The intermediate and non-classical monocytes seem to be more inflammatory [ 115 117 ] as has been shown also in other inflammatory diseases (e.g., heart failure [ 109 , 118 , 119 ]), as well as in aging per se [ 120 124 ], however this was not the case in studies where no change at the basal level was found [ 125 ]. This increased propensity to higher inflammatory phenotype has been attributed to the expression of CD16 by both intermediate and non-classical monocytes, which were suggested to resemble the senescent monocyte population with increased inflammatory potential due to their SASP state [ 122 124 ].…”
Section: Discussionmentioning
confidence: 97%
“…We found that the proportions of non-classical monocytes increased through the spectrum of AD from SMC to AD, while the intermediate monocyte subset increased only in MCI and AD patients at the expense of classical monocytes. The intermediate and non-classical monocytes seem to be more inflammatory [ 115 117 ] as has been shown also in other inflammatory diseases (e.g., heart failure [ 109 , 118 , 119 ]), as well as in aging per se [ 120 124 ], however this was not the case in studies where no change at the basal level was found [ 125 ]. This increased propensity to higher inflammatory phenotype has been attributed to the expression of CD16 by both intermediate and non-classical monocytes, which were suggested to resemble the senescent monocyte population with increased inflammatory potential due to their SASP state [ 122 124 ].…”
Section: Discussionmentioning
confidence: 97%
“…Monocytes [ 8 ] and other leucocytes play important roles in chronic inflammatory processes [ 38 ]. Low total monocyte counts have been shown in several studies, which noted an association with the increased risk for mortality in HF patients [ 39 , 40 , 41 ]. However, more studies have supported an association of increasing monocyte count with worse outcomes [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A reason why different studies present conflicting results may be because of different subsets of monocytes being predominant in CHF groups [ 39 ]. One work showed that Mon 3 gradually increased in NYHA groups ( p = 0.0002) and negatively correlated with LVEF (r = −0.628, p = 0.022) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LMR has been proposed as a surrogate marker for inflammation and has prognostic value too [18][19][20]. Further, an abnormal monocyte or lymphocyte count has been shown to have an adverse effect on the prognosis of various diseases [21,22]. In the field of obstetrics, there have been several studies regarding the association between CBC parameters and obstetric complications in addition to the ability of CBC to predict preterm birth.…”
Section: Discussionmentioning
confidence: 99%